South Sudanese and Syrian Refugee Community-based Organizations in Egypt: Contributions to Resilience and Reduction of Socioeconomic Vulnerabilities - Kasmo, Alaa (AUC Knowledge Fountain, 2023)
Community-based organizations (CBOs) have emerged as crucial actors in aid delivery of global efforts, including in Egypt, where they have gained recent attention. However, CBOs’ contributions to supporting displaced communities in Egypt must be adequately investigated. This thesis examines aspects of these contributions to resilience and the reduction of socioeconomic vulnerabilities for displaced communities in Egypt. The qualitative research approach presents comprehensive case studies of interviews and focus group discussions with CBO leaders and communities, providing data on four of the Syrian and South Sudanese CBOs and their communities’ experiences and perspectives on these contributions. CBOs enhance resilience and reduce socioeconomic vulnerabilities for displaced communities by capitalizing on social capital and networks. Through capacity-building in education and sustainable livelihoods, advocacy, and service provision, CBOs strengthen displaced communities’ opportunities, including women and youth. They provide a platform for community participation and engagement, promoting social cohesion and networking among community members. This thesis also illustrates the difficulties CBOs in Egypt confront, such as a lack of funding, administrative roadblocks, and a requirement for recognition and assistance from those involved in the aid distribution process. The qualitative method enabled a deeper investigation of these issues and gave a complete grasp of the intricate dynamics that influence CBOs' roles in Egypt. This thesis advances knowledge of CBOs' function in Egypt's efforts to distribute aid. The results have repercussions for professionals working to advance community-based methods of developing assistance for displaced populations.